Rapid duplex flap probe-based isothermal assay to identify the Cryptococcus neoformans and Cryptococcus gattii - Ye, Xin; Zhang, Lei; Yang, Qingqing; Pan, Weihua; Zeng, Xiaoyan (Frontiers in Cellular and Infection Microbiology, 2024)
Cryptococcosis is a life-threatening invasive fungal infection with significantly increasing mortality worldwide, which is mainly caused by Cryptococcus neoformans and Cryptococcus gattii. These two species complexes have different epidemiological and clinical characteristics, indicating the importance of accurate differential diagnosis. However, the clinically used culture method and cryptococcal capsular antigen detection couldn’t achieve the above goals. Herein, we established a novel duplex flap probe-based isothermal assay to identify the Cryptococcus neoformans and Cryptococcus gattii within 1 hour. This assay combined the highly sensitive nucleic acid isothermal amplification and highly specific fluorescence probe method, which could effectively distinguish the sequence differences of the two species complexes using two different fluorescence flap probes in a single reaction system. This novel method showed excellent detection performance with sensitivity (10 copies/μL each) and specificity (100%) compared to traditional culture and sequencing methods. Furthermore, we applied this method to spiked clinical samples, 30 cerebrospinal fluids and 30 bronchoalveolar lavage fluids, which kept good detection performance. This novel rapid duplex flap probe-based isothermal assay is a promising and robust tool for applications in differential diagnosis of the Cryptococcus neoformans and Cryptococcus gattii in clinical settings, especially when clinical suspicion for cryptococcal disease is high and epidemiological studies.